2001
DOI: 10.1175/1520-0493(2001)129<1500:leotdc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Land Effect on the Diurnal Cycle of Clouds over the TOGA COARE Area, as Observed from GMS IR Data

Abstract: The diurnal cycle of clouds over the western equatorial Pacific region (15ЊS-15ЊN, 130ЊE-180Њ) is studied analyzing hourly GMS-4 infrared brightness temperature images during the intensive observation period (Nov 1992-Feb 1993) of TOGA COARE. Although the area studied is essentially (93%) oceanic, differences of diurnal behavior of the clouds are noticed over different ocean subareas, depending both on the general circulation conditions and on the vicinity of landmasses. This study focuses on the effects of Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 37 publications
(59 reference statements)
5
46
0
2
Order By: Relevance
“…These high rainfall rates are concentrated along a relatively linear stretch of coastline where there is no enhanced localised convergence from colliding land breezes. Interestingly, the location of these rainfall rates coincides well with the offshore maximum in diurnal brightness temperature difference reported by Liberti et al (2001) (their Fig. 4), who documented the life cycle of convective cloudiness for New Guinea using infrared satellite data.…”
Section: Spatial Distributionsupporting
confidence: 84%
“…These high rainfall rates are concentrated along a relatively linear stretch of coastline where there is no enhanced localised convergence from colliding land breezes. Interestingly, the location of these rainfall rates coincides well with the offshore maximum in diurnal brightness temperature difference reported by Liberti et al (2001) (their Fig. 4), who documented the life cycle of convective cloudiness for New Guinea using infrared satellite data.…”
Section: Spatial Distributionsupporting
confidence: 84%
“…• Whereas other studies have shown a similar propagation signal in satellite data (e.g., Yang and Slingo 2001;Liberti et al 2001;Mapes et al 2003b), the propagation signal over the northern SCS was shown to exist similarly in both satellite and radar data, with both phase and propagation speed in agreement. Propagation was also implied by the increase in the stratiform fraction of convective systems moving southward away from the coast, suggesting maturing MCSs as they move southward.…”
Section: Discussionmentioning
confidence: 55%
“…This is defined as a "propagation signal," or a systematic variation of the phase of maximum convective activity with a coherent spatial structure. Other recent studies have provided observational evidence of propagation signals in the Bay of Bengal (Yang and Slingo 2001;Webster et al 2002;Zuidema 2003) and off the northern coast of New Guinea (Liberti et al 2001;Zhou and Wang 2006). In the latter study, Zhou and Wang found that gravity waves generated by deep convective heating over the mountains of New Guinea help to initiate rainbands in the coastal regions offshore.…”
Section: Introductionmentioning
confidence: 92%
“…The land-water interface drives convection initiation and thereby affects the spatial distribution of convection (Zuidema 2003). Cloud systems propagate northward from the northern coast of New Guinea; these propagating cloud systems arise from low-level convergence between the large-scale flow and a land breeze (Liberti et al 2001). Mapes et al (2003a, b) and Warner et al (2003) described observational and numerical studies of westward rainfall peak migration to offshore regions in the night time over northwestern South America.…”
Section: Introductionmentioning
confidence: 99%